Pengaruh Perubahan Debit Banjir Periode Ulang 25 Tahun Akibat Sedimentasi Pada Sub Das Karang Asam Kecil di Kota Samarinda - Yayuk Sri Sundari; Viva Oktaviani (Kurva S : Jurnal Keilmuan dan Aplikasi Teknik Sipil, 2019)
For soil types in the Karang Asam Sub Watershed, it is a subtle material resulting from river sedimentation. The effect of biophysical conditions on land cover / land use on sedimentation is very influential when the flood discharge rises because there is no holding river so that the surface water flow becomes large and erosion occurs which results in sedimentation in the river so that the capacity of the river falls due to land use changes that occur erosion resulting in sedimentation into the river so that the capacity of the river is reduced. Reduction in river flow capacity can be caused by sedimentation originating from sedimentation in the River due to the absence of cover vegetation and the improper use of land. The results of the analysis of total sediment transport for all fractions (QB) using the Einstein formula in the Main River of Karang Asam Kecil obtained QB = 0.054 m3 / s, so that the results of this sediment transport are thought to cause siltation / sedimentation which can reduce the water holding capacity of the river.